Multifocal Desmoplastic Infantile Ganglioglioma/Astrocytoma (DIA/DIG): An Institutional Series Report and a Clinical Summary of This Rare Tumor - Wang, Qiguang; Meng, Jinli; Cheng, Jian; Zhang, Si; Hui, Xuhui; Li, Qiang; Liu, Wenke; Ju, Yan; Sun, Lin (Frontiers in Oncology, 2022)
Aim: Multifocal desmoplastic infantile ganglioglioma/astrocytoma (DIA/DIG) has rarely been reported. Here, two cases have been presented, reviewing the literature and proposed treatment algorithms for this rare tumor. Patients and Methods: We report two patients diagnosed with multifocal DIA/DIGs in West China Hospital. In addition, a literature review was performed, in October 2019, on case reports of DIA/DIGs with multifocal lesions. The clinical and radiological features, treatment, and outcome of this rare disease were discussed. Results: DIA/DIGs with multifocal locations were rare, and only thirteen cases (including ours) had been reported. This series included 8 males and 5 females with a mean age of 31.4±45.7 months (range, 3-144 months). The supratentorial hemisphere, suprasellar region, posterior cranial fossa, and spinal cord were frequently involved. Ten patients (76.9%) received surgical resection for the symptomatic lesions and three patients (23.1%) underwent biopsy. Seven patients received chemotherapy postoperatively. Six individuals had tumor recurrences during the follow-up period, while three patients had tumors that spontaneously regressed. Finally, two patients died of tumor progression and one patient died of respiratory insufficiency and hypothalamic dysfunction. Conclusions: Multifocal DIA/DIGs have more aggressive clinical behavior and poor outcome despite benign histology. DIA/DIGs should be included in the differential diagnosis of multifocal brain tumors in children. The mainstay of treatment is surgical resection; adjuvant treatment with chemotherapeutic drugs is unknown and requires additional research.